Response Time Distributions in Rapid Chess: A Large-Scale Decision Making Experiment - Sigman, Mariano; Etchemendy, Pablo; Fernandez Slezak, Diego; Cecchi, Guillermo A. (Frontiers in Neuroscience, 2010)
Rapid chess provides an unparalleled laboratory to understand decision making in a natural environment. In a chess game, players choose consecutively around 40 moves in a finite time budget. The goodness of each choice can be determined quantitatively since current chess algorithms estimate precisely the value of a position. Web-based chess produces vast amounts of data, millions of decisions per day, incommensurable with traditional psychological experiments. We generated a database of response times and position value in rapid chess games. We measured robust emergent statistical observables: 1) Response time (RT) distributions are long-tailed and show qualitatively distinct forms at different stages of the game, 2) RT of successive moves are highly correlated both for intra- and inter-player moves. These findings have theoretical implications since they deny two basic assumptions of sequential decision making algorithms: RTs are not stationary and can not be generated by a state function. Our results also have practical implications. First, we characterized the capacity of blunders and score fluctuations to predict a player strength, which is yet an open problem in chess softwares. Second, we show that the winning likelihood can be reliably estimated from a weighted combination of remaining times and position evaluation.